2019
DOI: 10.3390/su11164477
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for Volunteerism, Satisfaction, and Emotional Exhaustion: The Moderating Effect of Volunteers’ Age

Abstract: This investigation aims to explore the moderating role of volunteers’ age in the relation between motivations for volunteering and, respectively, satisfaction with volunteerism and emotional exhaustion. A longitudinal study was conducted with a sample of 241 Spanish healthcare volunteers. Results show that volunteers’ age moderates the relations between social motivations and satisfaction, and social motivations and volunteers’ emotional exhaustion, and also between growth motivations and satisfaction, and vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
2
18
1
Order By: Relevance
“…In the Japanese context, Sakurai [ 29 ] examined the association between volunteer motives for participation and (1) the characteristics of target activities and (2) volunteer attributes such as age and sex; altruistic motives were found to have greater influence than self-oriented motives on older volunteers’ willingness to continue in service. A similar finding is reported in a study conducted in Spain, which found that among senior volunteers “social” (altruistic) motivation exerted stronger influence on volunteer satisfaction than self-oriented motivation, but not among young volunteers [ 30 ].…”
Section: Introductionsupporting
confidence: 85%
“…In the Japanese context, Sakurai [ 29 ] examined the association between volunteer motives for participation and (1) the characteristics of target activities and (2) volunteer attributes such as age and sex; altruistic motives were found to have greater influence than self-oriented motives on older volunteers’ willingness to continue in service. A similar finding is reported in a study conducted in Spain, which found that among senior volunteers “social” (altruistic) motivation exerted stronger influence on volunteer satisfaction than self-oriented motivation, but not among young volunteers [ 30 ].…”
Section: Introductionsupporting
confidence: 85%
“…Volunteering is not just about giving. We do not just give our services but also get so much in return in a bilateral process 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Volunteering provides chances for college students to develop their social media platforms to improve their curricula and increase their personality-confidence through an exchange experience 26 . Volunteering requires skills, time, money and above all passion and courage.…”
Section: Discussionmentioning
confidence: 99%
“…Philanthropic behavior and social demographics as an antecedent may be able to be explained by social support theory. In Surrogate terms, social support theory becomes the theoretical underpinnings of volunteering, which can be influenced by social demographics and motivation (Aranda et al, 2019). Philanthropic behavior is a different concept from volunteering, although several papers mention those correlations.…”
Section: Discussionmentioning
confidence: 99%